Emerging voices : the West Indian, Dominican and Haitian diasporas in the United States - Payne, Douglas W. (Centre for Strategic & International Studies WashingtonUS, 1998)
Provides an overview of the three diasporas, including their dimensions, who the people are, and when they came. Examines levels of insititutional development and considers the prospects for political empowerment and building influence in Washington.